Effects of coagulation factor VII polymorphisms on warfarin sensitivity and responsiveness in Jordanian cardiovascular patients during the initiation and maintenance phases of warfarin therapy - AL-Eitan LN; Almasri AY; Al-Habahbeh SO (Dove Medical Press, 2019)
Laith N AL-Eitan,1,2 Ayah Y Almasri,1 Sahar O Al-Habahbeh1 1Department of Applied Biological Sciences, Jordan University of Science and Technology, Irbid 22110, Jordan; 2Department of Biotechnology and Genetic Engineering, Jordan University of Science and Technology, Irbid 22110, Jordan Purpose: This study aims to investigate the relationships between genetic polymorphisms of the coagulation factor VII (FVII) gene and warfarin responsiveness and sensitivity. Patients and methods: The study population consisted of 417 subjects (207 Jordanian cardiovascular patients and 210 healthy individuals). Cardiovascular patients were classified into two groups: those sensitive to warfarin dosage (sensitive, moderate, and resistant) and those responsive to warfarin based on International Normalized Ratios (INRs; poor, good, and extensive responders). The HVR4 polymorphism of the FVII gene was genotyped. Results: Our results showed that there are significant differences between patients and controls according to both genotypic and allelic frequencies (P<0.0001) in the genetic susceptibility study. Moreover, the pharmacogenetics study reported that HVR4 had no association with warfarin sensitivity or responsiveness during the initiation and maintenance phases of therapy, the only significant differences were in the INR outcome measured during the maintenance phase of therapy (P=0.012). Conclusion: Our data suggests lacking of association between the HVR4 polymorphism in the FVII gene and warfarin sensitivity and responsiveness during the initiation and maintenance phases of therapy. It is possible that these patients carry additional mutations in genes involved in the coagulation pathway. Keywords: HVR4 polymorphism, cardiovascular disease, pharmacogenetics study